Left trisectionectomy combined with resection of the right hepatic vein and inferior vena cava after right hepatic vein embolization for advanced intrahepatic cholangiocarcinoma - Toshihiro Suzuki; Tomoki Ebata; Yukihiro Yokoyama; Takashi Mizuno; Tsuyoshi Igami; Junpei Yamaguchi; Shunsuke Onoe; Nobuyuki Watanabe; Masato Nagino (Surgical Case Reports)
Abstract Background When the inferior right hepatic vein (IRHV) is present, left hepatic trisectionectomy with resection of the right hepatic vein (RHV) is theoretically possible without reconstruction of the RHV. We here report a successful case of this extended hepatectomy after RHV embolization for advanced intrahepatic cholangiocarcinoma. Case presentation A 71-year-old man was admitted to our clinic with abdominal pain. Computed tomography showed a cholangiocarcinoma located at the caudate lobe that involved the inferior vena cava (IVC) and the roots of the three major hepatic veins. Portal vein embolization of the left and right anterior portal veins was performed. As the IRHV was present but thin, RHV was also embolized. Left hepatic trisectionectomy with resection of the involved IVC and RHV, preserving the IRHV, was done. The IVC was reconstructed with artificial graft. The patient was discharged on postoperative day 36. Conclusion RHV embolization is useful in extended left trisectionectomy with resection of the RHV when the IRHV is present but thin.